TINGKAT PERTUMBUHAN DAN PRODUKSI TANAMAN KENTANG (Solanum tuberosum L) PADA SISTEM PERTANIAN ORGANIK - Muhammad Sugiarto (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2012)
The experiment was conducted in the village of Karya Manunggal, District Randangan, Pohuwato District, Gorontalo Province which runs from April to July 2012. This study was conducted in the form of trials organized by RAK (randomized block design). Using chicken manure 06 kg / plant combined with a dose of liquid fertilizer biofid as follows: control (B0), 5 cc Biofid (B1), 10 cc Biofid (B2), 15 cc Biofid (B3). The results showed that treatment of 15 cc very real influence on the growth and production of potato crop.